Discharge planning from hospital to home. - Shepperd, S; Parkes, J; McClaren, J; Phillips, C (2004)
BACKGROUND: Discharge planning is a routine feature of health systems in many countries. The aim is to reduce hospital length of stay and unplanned readmission to hospital, and improve the co ordination of services following discharge from hospital thereby bridging the gap between hospital and place of discharge. Sometimes discharge planning is offered as part of an integrated package of care, which may cover both the hospital and community. The focus of this review is discharge planning that occurs while a patient is in hospital; we exclude studies that evaluate discharge planning with follow up care. OBJECTIVES: To determine the effectiveness of planning the discharge of patients moving from hospital. SEARCH STRATEGY: Relevant studies were identified using Medline, Embase, SIGLE database for grey literature, Bioethics database, Health Plan, Psych. Lit, Sociofile, CINAHL, Cochrane Library, Econ Lit, Social Science Citation Index, EPOC register. The review was updated using the EPOC trials register in August 2002. SELECTION CRITERIA: STUDY DESIGN: randomised controlled trials (RCTs) that compare discharge planning (the development of an individualised discharge plan) with routine discharge care. PARTICIPANTS: all patients in hospital. INTERVENTION: the development of an individualised discharge plan. DATA COLLECTION AND ANALYSIS: Data analysis and quality assessment was undertaken independently by two reviewers using a data checklist. Studies are grouped according to patient group (elderly medical patients, surgical patients, and those with a mix of conditions), and by outcome. MAIN RESULTS: Three new studies were included in this update. In total we included eleven RCTS: 6 trials recruited patients with a medical condition (2,368 patients), and four recruited patients with a mix of medical and surgical conditions (2,983 patients), one of these four recruited medical and surgical patients as separate groups, and the final trial recruited 97 patients in a psychiatric hospital and from a general hospital. We failed to detect a difference between groups in mortality for elderly patients with a medical condition (OR 1.44 95% CI 0.82 to 2.51), hospital length of stay (weighted mean difference -0.86, 95% CI -1.9 to 0.18), readmission rates (OR 0.91 95% CI 0.67 to 1.23) and being discharged from hospital to home (OR 1.15 95% CI 0.72 to 1.82). This was also the case for trials recruiting patients recovering from surgery and those recruiting patients with a mix of medical and surgical conditions. One trial comparing a structured care pathway for patients recovering from a stroke with multidisciplinary care reported a significant rate of improvement in functional ability and quality of life for the control group (median change in Barthel score between 4 to 12 weeks of 2 points for the treatment group, versus 6 for the control group, p<0.01); (Euroqol scores at 6 months 63 for the treatment group, vs. 72 for the control group, p<0.005). Two trials reported that patients with medical conditions allocated to discharge planning reported increased satisfaction compared with those who received routine discharge. No statistically significant differences were reported for overall health care costs. REVIEWER'S CONCLUSIONS: The impact of discharge planning on readmission rates, hospital length of stay, health outcomes and cost is uncertain. This reflects a lack of power as the degree to which we could pool data was restricted by the different reported measures of outcome. It is possible that even a small reduction in length of stay, or readmission rate, could have an impact on the timeliness of subsequent admissions in a system where there is an shortage of acute hospital beds.